Tax Incentive, Ease of doing Business and Environmental Sustainability of SMES in Nigeria - Ogundajo, Grace Oyeyemi; Aguguom, Theophilus Anaekenwa; Abiola, Oluwatobi Ayodele; Akinpelu, Olumide Olayiwola (International Review of Management and Marketing, 2026)
This study investigates the effect of tax incentives, ease of doing business, and environmental sustainability of small and medium enterprises (SMEs), considering the moderating role of ease of doing business. The study sampled 387 SMEs using Taro Yamane from the population of 11,663 SMEs owners in Lagos, Nigeria. The study employed a field survey research design, using an online structured questionnaire administered to SME owners. The instrument’s validity and reliability were based on KMO, Bartlett’s test of sphericity, and Cronbach’s alpha test. Both descriptive and inferential methods of data analysis were adopted in the study. The findings revealed that most participants agree that tax incentives and ease of doing business deepen environmental sustainability. Furthermore, the study found that tax incentives collectively play an important role in influencing environmental sustainability, while ease of doing business significantly moderated the effect of tax incentives on environmental sustainability. The practical implication of this study informs the government and tax administrators to prioritize tax incentives for SMEs. The findings are expected to encourage policymakers to initiate tax reforms and legal framework tax initiatives to ease of doing business and implement tax incentive reforms to enhance the environmental sustainability of SMEs in Nigeria.